Creative Crowds Perspektiven der Fanforschung im deutschsprachigen Raum - Cuntz-Leng, Vera (Büchner-Verlag, 2014)
The notion of fans as hysterical teenagers, aggressive hooligans or nerdy loners has changed drastically. Whereas Trekkies, live-action role-players or Gothics were still viewed critically a few years ago, today everyone debates the »Hobbit« movies or the new »Sherlock« season and can buy their Ramones shirt at the discount store. Thanks to the Internet, fans have not only arrived in the mainstream, but have also become more mature and creative. For a long time now, they have not only devoted themselves to the adoration of their favorite characters and idols, they have also conquered a place in pop culture for themselves and their creative output. This volume brings together contributions from various disciplines on a multifaceted spectrum of fandoms, fan cultures, and fan creations in the German-speaking world: from soccer stadiums to online forums, from cosplayers to vidders, from Prince to »Twilight«.